2019
DOI: 10.3389/fgene.2019.00393
|View full text |Cite
|
Sign up to set email alerts
|

On the Complexity of Mechanisms and Consequences of Chromothripsis: An Update

Abstract: In the present review, we focus on the phenomenon of chromothripsis, a new type of complex chromosomal rearrangements. We discuss the challenges of chromothripsis detection and its distinction from other chromoanagenesis events. Along with already known causes and mechanisms, we introduce aberrant epigenetic regulation as a possible pathway to chromothripsis. We address the issue of chromothripsis characteristics in cancers and benign tumours, as well as chromothripsis inheritance in cases of its occurrence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 137 publications
(183 reference statements)
1
56
0
1
Order By: Relevance
“…The key-features, common to all chromothripsis events are the occurrence of numerous clustered chromosomal breakpoints, the low DNA copy number changes and the preservation of heterozygosity in the rearranged segments [14,15]. Several mechanisms involving telomere attrition, mitotic errors, abortive apoptosis, premature chromosome condensation, p53 defect, or viral integration were identified as cellular processes driving chromothripsis [16][17][18][19][20]. An attractive mechanistic explanation to link all these causal processes with the confined nature of genomic alterations generated by chromothripsis, is that the implicated chromosome(s) can be sequestrated into a micronucleus in which chromothripsis-related damages will occur [21,22].…”
Section: All-in-onementioning
confidence: 99%
“…The key-features, common to all chromothripsis events are the occurrence of numerous clustered chromosomal breakpoints, the low DNA copy number changes and the preservation of heterozygosity in the rearranged segments [14,15]. Several mechanisms involving telomere attrition, mitotic errors, abortive apoptosis, premature chromosome condensation, p53 defect, or viral integration were identified as cellular processes driving chromothripsis [16][17][18][19][20]. An attractive mechanistic explanation to link all these causal processes with the confined nature of genomic alterations generated by chromothripsis, is that the implicated chromosome(s) can be sequestrated into a micronucleus in which chromothripsis-related damages will occur [21,22].…”
Section: All-in-onementioning
confidence: 99%
“…The key difference between chromoanasynthesis and chromothripsis is that chromoanasynthesis harbors copy gains in addition to losses, whereas chromothripsis has almost complete absence of gains (14,38). Typically, chromoanasynthesis occurs in one or few chromosomes (12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, chromothripsis is mainly observed in chromosome arms, whereas centromeres were targeted in our studies 13 . However, some studies have indicated an association between chromothripsis break sites and the presence of transposon sequences 11, 60 . In our approach, the breaks were also located within transposon sequences, which are part of the centromeres.…”
Section: Discussionmentioning
confidence: 99%